Sleep apnea and comorbid diseases - a review - Guderska, Urszula; Urbanek, Agnieszka; Kurzeja, Jacek; Maciejewska, Danuta; Rasmus-Czternasta, Adrianna; Bartczak, Magdalena; Czternasty, Filip (Journal of Education, Health and Sport, 2024)
Obstructive sleep apnea (OSA) is a common disease spreading around the world. It is unavoidably linked to the increasing rate of obesity, particularly in Western societies. Associated higher prevalence of sleep disordered breathing has also been observed. There are many diseases that can lead to OSA and many that are a result of untreated OSA. From the widely known cardiovascular complications to indirectly related diseases, such as insomnia, Alzeihmer’s disease or psoriasis. Overall, sleep-disordered breathing have been shown to negatively impact quality of life, including general health perception, physical functioning, social functioning, and vitality. That is why it is important to spread awareness about OSA, often asymptomatic, through medical staff and patients in the risk group. In this review we describe the illness, the ways to diagnose it and discuss comorbid diseases.